Performance of Foreign Cane Germplasm on Florida Sandlands - Robert A. Gilbert; J. D. Miller; Jack C. Comstock; B. Glaz; Serge J. Edme (EDIS)
This document is SS-AGR-270, part of the Florida Sugarcane Handbook, published by the UF Agronomy Department, June - October 2007.